Optimalisasi Kepatuhan Minum Obat Lansia melalui Penggunaan Pillbox di Posyandu Plus RW 07 Serengan Surakarta - Niken Luthfiyanti; Vivin Marwiyati Rohmana; Ady Irawan A. M.; Aprilia Puteri Santika; Iza Zulfa Salsabila (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Older adults with degenerative diseases often experience poor medication adherence, increasing the risk of complications and reducing quality of life. At Posyandu Plus RW 07 Serengan, Surakarta, health services for older adults were limited to basic examinations and lacked structured medication monitoring and health education programs. This community service program aimed to improve medication adherence through the Early Detection of Degenerative Diseases and Integrated Pillbox Intervention Program (Pro-DegPill). The program consisted of cadre training, degenerative disease screening, health education, integrated pillbox utilization, mentoring, and evaluation. A total of 15 community health cadres and 54 older adults participated. Program effectiveness was assessed through pre- and post-intervention evaluations of knowledge, readiness, and medication adherence. The results showed a significant increase in cadres’ knowledge and readiness, from 56.63% to 89.16% (p = 0.001). Older adults’ knowledge of degenerative diseases also improved from 56.49% to 86.10% (p = 0.001). In addition, the integrated pillbox intervention significantly enhanced medication adherence. The proportion of participants with high adherence increased from 14.8% to 40.7%, while low adherence decreased from 44.4% to 14.8% (p < 0.000). The Pro-DegPill program effectively improved cadre capacity, increased older adults’ knowledge, and enhanced medication adherence among older adults with degenerative diseases. This intervention has the potential to serve as a community-based healthcare model supporting the implementation of Integrated Primary Healthcare Services (Posyandu ILP) to prevent complications of degenerative diseases in older populations.